Виявлення та повернення старожитностей як елемент державної політики по відновленню музейного фонду у перші повоєнні роки (1946–1947) (на матеріалах Харківського історико-краєзнавчого музею ім. Г. Сковороди) - Дейнеко, С.М. (Сіверщина в історії України, 2023)
Розвідка присвячена одній із маловідомих сторінок історії українського музейництва – відновленню колекції Харківського історико-краєзнавчого музею імені Г. Сковороди. Його збірка сильно постраждала у роки Другої світової війни, у принципі як і зібрання більшості подібних установ на території УРСР, тому уряд республіки прийняв низку рішень про якнайшвидше відновлення музейних колекцій. Одним із шляхів комплектування стало виявлення предметів старовини у юридичних та фізичних осіб і спроби вилучення цих коштовностей на користь музею. У дослідженні розглянуто результати роботи комісії по виявленню музейних цінностей у Харкові в 1946–1947 рр.: її склад, кількість обстежених організацій, тип виявлених предметів. At the end of World War II, the leadership of Soviet Ukraine, for the sake of fast restoration of the republic museum fund, together with other ways of collection renovation, initiated the replenishment of the collection due to the antiquities, which were owned by individuals and legal entities arguing that they have cultural and historical value and not being interested in legal issues of the question. In particular, in the property right and the documentary confirmation of their complaint to the property of individuals and legal entities. We assume that the purpose of this was not only the search and return of missing objects from the museum collections but also their replenishment owing to the antiquities, which have never belonged to the museum fund of the USSR. Special committees, which were created under the decision of the local authorities, have become an instrument for performing this decision. In Kharkiv, such a body was initially created in 1945, and this decision was duplicated in 1946. The committee included five people, who created a working group from the employees of Skovoroda Kharkiv museum of local history in number of twelve people. They inspected 296 different institutions and individuals in nine districts of the city. Among the found objects of antiquity prevailed furniture produced mainly in the XIX century, less common were paintings, documents, household items, and printed press.